The Implementation of Identity Branding in University Office Interior - Cherry Cher (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
Branding identity is an important element for every field of corporate institutions, one of which is engaged in the world of education. Branding identity can be in the form of logo elements, mascots, colors, taglines, vision, mission, goals, to characters agreed upon by the institution. Through all of these elements, identity can shape design concepts that are applied to interior spaces, both element that forming the space and element that filling the spaces. Branding identity, however, does not have to be visualized directly like color, through identity characters, designs can be transformed which is meaningful and bring the message to these identity characters. Through the interior redesign of the Petra Christian University office in the FHIK field, branding identity is implemented through character, color, purpose and tagline, which form a design concept. The design concept forms the interior design of the office, which is implemented on walls, partitions, windows, tables, chairs, panels, and the type of space. Key words : brand identity, office, room